BiVO4 powder synthesized via the solvothermal method - Pongthep Jansanthea (2018)
Bismuth vanadate (BiVO4) powder was synthesized via the solvothermal method at 100- 200 °C for 2-6h by using acetic acid as solvent without calcination steps. The phase transition of BiVO4 powder was studied by X-ray diffraction (XRD). The morphology and chemical composition of BiVO4 powder were investigated by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The functional groups of BiVO4 powder was identified by Fourier transform infrared spectroscopy (FTIR). © (2014) Trans Tech Publications, Switzerland.